Discourse on Intellectual Disability and Improved Access to Assistive Technologies in Malawi - Ngomwa, Peter Morris Gasten (Frontiers in Public Health, 2019)
• Assistive technologies are one of the five elements under the Health Component of the World Health Organization CBR Guidelines that Malawi is using to implement the Community Based Inclusive Development (CBID) Programme. • The technologies enhance independent living by removing barriers that come due to disability or old age and should, therefore, be prioritized. However, Malawi does not have a straightforward way of providing Assistive Technology. • Individuals are considered upon the assessment of their needs whose intervention with respect to assistive products may not be available. • This is mostly the case with persons with intellectual disabilities, in which there is very little expertise to work with, in Malawi, although they require assistive products to improve their quality of life just like other persons with disabilities. • There are many sectoral policies and laws in Malawi, nonetheless, they do not have a positive input on persons with intellectual disability to access assistive technologies in terms of availability (provision), affordability (cost) and appropriateness (suitability and quality). • Therefore, this paper intends to demonstrate the barriers that are faced by persons with intellectual disabilities, examine the policies and pieces of legislation that would have influenced better access and maps the way on how barriers can be removed to ensure that Assistive Technologies are readily and easily accessed.